Inter-subjects Running Dynamic Similarities in Men and Women - Delattre, N.; Lafortune, M. A.; Moretto, P. (Ninth International Symposium on the 3-D Analysis of Human Movement, June 28-30, 2006, Valenciennes, France, 2006)
The aim of this study is to test the validity of Froude number (NFr) or Strouhal number (Str) to determine intersubjects similar running patterns. Twenty male and eighteen female subjects ran barefoot on a runway equipped with a force platform. The running tests were performed in three experimental conditions. C0: all subjects ran at the same absolute velocity V=3.5 m.s-1; C1: the velocity was determined from the NFr ; C2: the stride frequency was determined from Str. In both men and women, the use of Strouhal number (C2) allowed obtaining the best correlations between anthropometric and kinetic similarity ratios i.e. the best dynamic similarities. However, it appears that the determination of similar dynamic running conditions needs to be specified in order to take leg stiffness into account. The simultaneous use of Froude and Strouhal numbers could bring better results in this way.